Sustainable Practices for Rice Agripreneurs - Stephanie Kim Ramos; Arly N. Visperas; Clarisse S. Vila; Lurene Myles V. Bernales; Aira Camille J. Cenizan; Jemyma Joyce M. Decenon; Mark Juven C. Sibucao (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study, "Sustainable Practices of Rice Agripreneurs," explores how rice agripreneurs in Villasis, Pangasinan, Philippines, integrate organic farming, modern farming techniques, and smart farming practices to enhance agricultural sustainability. Despite technological advancements, many farmers still face barriers such as limited capital, technical expertise, and training, creating a gap between traditional and innovative farming systems. The study employed a quantitative descriptive design using validated questionnaires administered to 35 registered rice agripreneurs in Villasis, Pangasinan, Philippines. Data were analyzed through frequency, percentage, weighted mean, and Pearson correlation to assess sustainable practices and their relationship with business profiles. This research is also anchored in the UN-SDGs 1, 2, 4, 10, 12, 15, and 17. Most respondents have extensive agribusiness experience and manage small to medium-sized farms, mainly on rented land. Modern farming techniques were the most practiced (AWM = 3.28), followed by organic farming (AWM = 2.89), while smart farming tools were only sometimes practiced (AWM = 2.21). These findings indicate that while agripreneurs adopt sustainable methods, technological practices remain limited. Moreover, results revealed no significant relationship between business profiles and sustainable practices, implying equal adoption regardless of experience or farm size. The study concludes that rice agripreneurs prioritize sustainability but need improved access to technology, funding, and institutional support. It recommends implementing GreenGrain: Empowering Sustainable Rice Agripreneurs for Inclusive Growth, an extension program that promotes education, digital literacy, and eco-friendly innovations to enhance productivity, profitability, and environmental resilience.